Absence of Rapid Exchange Component in a Low-Affinity Carrier Transport - LeFevre, Paul G. (The Rockefeller University Press, 1963)
A previous study showed that human red blood cells equilibrate much less rapidly with D-glucose at moderately high concentrations than with C(14)-glucose added after the net movement is completed. This had been predicted from a simple reversible mobile-carrier mediated-transport model system suggested by the net monosaccharide transport kinetics in these cells, but is also consistent with the more complex models proposed for certain active transport systems to account for elevation of tracer fluxes of even low-affinity "substrates" when their trans-concentration is raised. The simple model predicts, however, that with any sugar showing a much lower apparent affinity for the reactive sites, such as D-ribose, this phenomenon would not be observed, and tracer equilibration should proceed at approximately the same rate as net uptake. The latter expectation was confirmed experimentally by analyses of the ribose, or radioactivity, content of washed red cells sampled serially during incubation with ribose or C(14)-ribose in the appropriate mixtures. The tracer ribose movement showed no evidence of a relatively rapid exchange component. The relative rapidity of glucose tracer uptake into cells preloaded with ordinary glucose may therefore more readily be attributed simply to depression of tracer efflux by competition for the saturated reactive sites, than to any action of the trans-concentration on the influx by way of a coupled exchange process.